Encapsulation of Organic Dyes within an Electron‐Deficient Redox Metal‐Organic Tetrahedron for Photocatalytic Proton Reduction - Wang, Hailing; Li, Lili; Li, Xuezhao; He, Cheng (Israel journal of chemistry, 2019)
The design of artificial systems that mimic highly evolved and finely tuned natural photosynthetic systems is a subject of intensive research. By incorporating electron‐deficient anthraquinone within the ligand backbone, a redox‐active Ni‐based tetrahedron was developed as a redox vehicle for the construction of an artificial photosynthesis system. The tetrahedron can encapsulate fluorescein within its cavity for light‐driven H2 evolution, with the turnover number reaching 1200 moles H2 per mole redox catalyst. This well‐designed supramolecular system displayed a significantly superior activities compared with the reference mononuclear compound or introducing an inactive inhibitor (ATP), which confirmed this enzymatic photocatalytic behaviour. An redox‐active metal‐organic tetrahedron (Ni‐AFP) containing four Nickel ions and six anthraquinone ligands was developed to encapsulate organic dyes (fluorescein) through a host‐guest interaction for photocatalytic hydrogen production. Control experiments with a mononuclear complex (Ni‐DFP) as a reference photocatalyst and inactive ATP as an inhibitor were performed to confirm this enzymatic supramolecular photocatalytic behaviour.